Investigation of the reaction kinetics of o-phenylenediamine in the presence of Cu(II) - (:unkn) unknown (MARCEL DEKKER INC, 2003)
The reactions involving o-phenylenediamine (OPDA) in the presence of Cu(II) was studied and the reaction rate was found to be v=k[Cu2+]/[o-phen]. Using a perpetual change curve, the ratio of [Cu2+]/[o-phen] was found to be 1 : 1 The rate equations perpetual change curve demonstrates that one molecule of OPDA reacts with one Cu2+ ion and a monoimine is formed as the transfer of one electron occurs in the oxidation reaction.
Keywords: o-phenylenediamine (OPDA); reaction kinetics; oxidation of o-phenylenediamine; copper (II)